OPTIMALISASI SISTEM PENGAMBILAN KEPUTUSAN BERBASIS DATA DALAM MANAJEMEN STRATEGIS SEKOLAH DASAR - Susanto, Teguh Trianung Djoko; Rajagukguk, Handyka Oktra; Tambun, Albert; Sartika, Dian (STKIP Pesisir Selatan, 2025)
Most elementary schools still lack adequate technological infrastructure to support complex data management. Therefore, intensive training for principals on technology utilization and data analysis is a crucial step. This study examines the implementation of data-driven decision-making systems in strategic management in Indonesian elementary schools. Using a systematic literature review and the PRISMA protocol, 45 studies published between 2019 and 2024 were analyzed. Thematic analysis identified three main themes: principals’ data literacy, challenges of technological infrastructure, and the impact of transformational leadership. The findings highlight the need for professional training programs to enhance principals’ competencies and improve data utilization. The proposed Data-Driven Decision-Making Framework (D3F) aims to address these challenges and optimize strategic management in elementary schools. The study emphasizes the importance of integrating technology and evidence-based practices to strengthen decision-making processes in education.